A professional development practice to enhance principals' instructional leadership – enabling and constraining arrangements. Issue 4 (11th May 2021) - Liljenberg, Mette
Abstract : Purpose: The purpose of this paper is to increase the knowledge of principals' professional development (PD) by focusing on the arrangements that shape a PD practice initiated to enhance principals' instructional leadership. Design/methodology/approach: The paper draws on findings from a three-year PD initiative in a Swedish school district. The data consist of field notes and semi-structured interviews with principals and managers. Theoretically, the paper takes its starting point in the theory of practice architectures and the cultural-discursive, material-economic and social-political arrangements that shape practices. Findings: Practices for principals' PD require a fine balance to prevent the perception of hierarchical control. Designated time, common artifacts and external expertise are arrangements of practice that enable principals' PD. High expectations and relations between principals and managers both enable and constrain principals' PD. As trustful relations are of particular importance, the implication for managers and others organizing for principals' PD is to make sure that collaborative work settings also become a natural way of working for principals. As building relations takes time, a longer time perspective is also recommended. Practical implications: The findings have practical implications for educational leaders responsible for organizing PD practices for principals in any context. Originality/value: This paper adopts a practice theory approach to its study of principals' PD and provide an elaborated illustration of arrangements that enable and constrain principals' PD in collegial settings.